Pengembangan Sistem Penggerak Roda pada Mekanisme Kerja Alat Uji Suspensi Menggunakan Motor BLDC - Haliman Abrahan Junior Sumadi; Sri Sasmita Anugrah Putri; Simon Ka'ka; Mukhtar Mukhtar (Jurnal Teknik Mesin Sinergi, 2022)
On a four-wheeler it takes comfort in driving. Using functional suspension systems to maximize performance from vehicles. The specific function of suspension that consists of absorbing oscillation and surprise vibrations, supporting weights, maintaining geometric wheels, adding traction to the wheel, and carrying on the braking style. The BLDC motor is one of the types of synchronous motors where the magnetic field produced by the stator and the magnetic field produced by the rotor spins at the same frequency. In writing this final assignment was used by the BLDC motor in order to control the velocity of the propulsion system on a conveyor test device to move the belt conveyor. The motor BLDC is controlled by a high power brushledd controlled which has an average voltage of 48 [v], an average of 35 [a], and an average power of 1000 [w]. The power supply is supplied from a power supply capable of producing 50 [v] tension and a current of 30 [a]. The suspension test came with a 16x2 LCD to show a junction for the shock junction of the springs, and was equipped with logger data to store the junction when the current charge used a 1 - centimeter roadblock against the springs. The junction mostly comes in a suspension with a pressure of 1-3 [bar] which is 6.4 [mm]. Based on the research and discussions it may be concluded that suspension devices could move the wheels of vehicles with additional loads and fixed speed and could identify the junction with the body of vehicles using the logger data.